A method for recycling acrylonitrile-butadiene-styrene copolymer
Patent Information
- Application Number
- CN202610999645.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-07-07
AI Technical Summary
其中,机械回收虽然流程简单,但只能降级使用,难以恢复材料原有性能;密度分选能够提高混合塑料中的ABS固液分离效率,但并不直接产生高附加值产物;溶剂回收虽然可获得较纯净ABS,但其本质仍是“回收获得ABS”,未能进一步向平台化学品或功能高分子方向延伸
本发明提供一种回收丙烯腈-丁二烯-苯乙烯共聚物的利用方法,通过选用合适的催化剂和条件,使丙烯腈-丁二烯-苯乙烯共聚物的聚丁二烯橡胶相发生氧化断链从共聚物中脱离出来,经后处理获得具有更高附加值的丁二酸和/或羧酸化丙烯腈-苯乙烯共聚物,实现了废旧塑料向其他高附加值产物的有效转化。
Smart Images

Figure CN122520974B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer material recycling technology, and more specifically, to a method for recycling and utilizing acrylonitrile-butadiene-styrene copolymer. Background Technology
[0002] Acrylonitrile-butadiene-styrene copolymer (ABS) is a typical multiphase engineering plastic composed of a styrene-acrylonitrile continuous phase (SAN) and a polybutadiene rubber phase (PB). It combines rigidity, toughness, and processability, and is widely used in home appliances, electronics, automotive parts, and daily necessities. With the continuous increase in the amount of waste ABS, its high-value utilization has become a key issue in the recycling of engineering plastics.
[0003] Currently, ABS recycling mainly includes mechanical recycling, density sorting, and solvent recovery. Among them, mechanical recycling, although simple in process, can only be used in a downgraded manner and it is difficult to restore the original properties of the material; density sorting can improve the solid-liquid separation efficiency of ABS in mixed plastics, but it does not directly produce high-value-added products; although solvent recovery can obtain relatively pure ABS, its essence is still "recycling to obtain ABS", and it has not been further extended to platform chemicals or functional polymers.
[0004] On the other hand, existing research on the chemical recycling of polymers mainly focuses on polyolefins, polyesters, or general unsaturated polymers. These technologies either aim for complete oxidation to obtain small-molecule chemicals, making it difficult to retain valuable polymer segments, or rely on bromine-containing catalytic systems, leading to problems such as equipment corrosion and complex wastewater management. However, for multiphase copolymers like ABS, the chemical recycling process is even more challenging: the overall oxidation behavior is extremely complex and difficult to control precisely, especially since the rubber phase is prone to over-oxidation. Even using a direct, complete oxidation approach, the resulting small-molecule carbonyl compounds are mostly low-value products, making them economically unfeasible. Therefore, there is an urgent need to develop a new utilization method for ABS to upgrade and transform waste plastics into high-value-added products. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a method for utilizing recycled acrylonitrile-butadiene-styrene copolymer. This method processes the recycled acrylonitrile-butadiene-styrene copolymer, converting it into other high-value-added products.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for utilizing recycled acrylonitrile-butadiene-styrene copolymer, the method comprising the following steps: S1. Dissolve or swell the recovered acrylonitrile-butadiene-styrene copolymer with a polar aprotic solvent, and add a cobalt catalyst that can dissolve in a polar aprotic solvent to obtain the reaction precursor; S2. In an oxygen-containing gas atmosphere, the reaction precursor is subjected to an oxidative chain scission reaction at 130~180 ℃. After the reaction is completed, it is cooled to room temperature in an inert atmosphere. S3. The system is separated and purified to obtain succinic acid and / or carboxylated acrylonitrile-styrene copolymer.
[0007] The inventors discovered that by dissolving or swelling recycled acrylonitrile-butadiene-styrene copolymer (ABS), and then using a cobalt catalyst soluble in polar aprotic solvents at a specific temperature, the polybutadiene segments in the ABS undergo oxidative chain scission, generating extractable small-molecule dicarboxylic acids. Simultaneously, the acrylonitrile-styrene segments are retained, and carboxylated structures are introduced at their ends. Subsequent processing yields succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively. This invention provides a method for converting waste plastics into other high-value-added products.
[0008] In this invention, the "swelling" mentioned in step S1 refers to immersing the polymer material in a solvent, allowing it to absorb the solvent until its volume no longer changes, and the polymer material has no hard core or clumps inside. Through the dissolution or swelling in step S1, a homogeneous or quasi-homogeneous system is formed.
[0009] In this invention, the polymer material is in the form of powder or granules.
[0010] In this invention, the carboxylated acrylonitrile-styrene copolymer refers to an acrylonitrile-styrene copolymer with an acrylonitrile-styrene copolymer segment as the main chain and terminal carboxylic acid groups.
[0011] In this invention, the term "acrylonitrile-butadiene-styrene copolymer" (ABS) refers to a polymer material having a multiphase structure of styrene-acrylonitrile continuous phase (SAN) and polybutadiene rubber phase (PB).
[0012] In this invention, the source of the recycled acrylonitrile-butadiene-styrene copolymer is not particularly limited. For example, it can be virgin acrylonitrile-butadiene-styrene copolymer, industrially recycled acrylonitrile-butadiene-styrene copolymer, or post-consumer recycled acrylonitrile-butadiene-styrene copolymer.
[0013] In this invention, the term "virgin acrylonitrile-butadiene-styrene copolymer" refers to: acrylonitrile-butadiene-styrene copolymer that has not been recycled.
[0014] In this invention, the term "post-industrial recycled acrylonitrile-butadiene-styrene copolymer" refers to acrylonitrile-butadiene-styrene copolymer that is recycled during the manufacture of a commodity or product or before delivery to a consumer.
[0015] In this invention, the term "post-consumer recycled acrylonitrile-butadiene-styrene copolymer" refers to acrylonitrile-butadiene-styrene copolymer recovered after a commodity or product has been used and discarded by a consumer.
[0016] Preferably, the polar aprotic solvent is one of pyrrolidone solvents, amide solvents, or sulfoxide solvents.
[0017] Specifically, the pyrrolidone solvent may be N-methylpyrrolidone, N-ethylpyrrolidone, etc.
[0018] Specifically, the amide solvent may be N,N-dimethylformamide, N,N-dimethylacetamide, etc.
[0019] Specifically, the sulfoxide solvent may be dimethyl sulfoxide.
[0020] Among them, pyrrolidone solvents have good solubility for the recovered acrylonitrile-butadiene-styrene copolymer and can achieve dissolution.
[0021] Amide or sulfoxide solvents are less effective than pyrrolidone solvents in recovering acrylonitrile-butadiene-styrene copolymers, but they can still be used to recover the swelling of acrylonitrile-butadiene-styrene copolymers.
[0022] To facilitate a better reaction, pyrrolidone solvents are preferred as polar aprotic solvents.
[0023] More preferably, the polar aprotic solvent is N-methylpyrrolidone.
[0024] Preferably, the mass-to-volume ratio of the recovered acrylonitrile-butadiene-styrene copolymer to the polar aprotic solvent is 1 g: 10~40 mL.
[0025] Optionally, the mass-to-volume ratio of the recovered acrylonitrile-butadiene-styrene copolymer to the polar aprotic solvent is one or any two of the following: 1 g: 10 mL, 1 g: 12 mL, 1 g: 14 mL, 1 g: 16 mL, 1 g: 18 mL, 1 g: 20 mL, 1 g: 22 mL, 1 g: 24 mL, 1 g: 26 mL, 1 g: 28 mL, 1 g: 30 mL, 1 g: 32 mL, 1 g: 34 mL, 1 g: 36 mL, 1 g: 38 mL, 1 g: 40 mL.
[0026] More preferably, the mass-to-volume ratio of the recovered acrylonitrile-butadiene-styrene copolymer to the polar aprotic solvent is 1 g: 20~30 mL.
[0027] Preferably, the cobalt catalyst that can dissolve in polar aprotic solvents is an inorganic cobalt compound or an organic cobalt compound.
[0028] It should be noted that any inorganic cobalt compound that has catalytic activity and is soluble in polar aprotic solvents is applicable to this invention, such as, but not limited to, one or more of cobalt chloride, cobalt bromide, or cobalt nitrate. Preferably, the inorganic cobalt compound is cobalt chloride.
[0029] It should be noted that any organocobalt compound that has catalytic activity and is soluble in polar aprotic solvents is applicable to this invention, such as, but not limited to, one or both of cobalt carboxylates or cobalt complexes. Preferably, the organocobalt compound is a cobalt carboxylate.
[0030] Optionally, the cobalt carboxylate is one or more of cobalt acetate, cobalt acetate tetrahydrate, cobalt formate, or cobalt isooctanoate. Cobalt acetate is preferred.
[0031] Preferably, the amount of the cobalt catalyst soluble in polar aprotic solvent is 0.5 to 10 wt% of the mass of the recovered acrylonitrile-butadiene-styrene copolymer.
[0032] Optionally, the amount of the cobalt catalyst soluble in the polar aprotic solvent is within one or any two of the following ranges based on the mass of the recovered acrylonitrile-butadiene-styrene copolymer: 0.5 wt%, 1.0 wt%, 1.5 wt%, 2.0 wt%, 2.5 wt%, 3.0 wt%, 3.5 wt%, 4.0 wt%, 4.5 wt%, 5.0 wt%, 5.5 wt%, 6.0 wt%, 6.5 wt%, 7.0 wt%, 7.5 wt%, 8.0 wt%, 8.5 wt%, 9.0 wt%, 9.5 wt%, and 10.0 wt%.
[0033] More preferably, the amount of the cobalt catalyst soluble in polar aprotic solvent is 3 to 7 wt% of the mass of the recovered acrylonitrile-butadiene-styrene copolymer.
[0034] Preferably, in S1, the dissolution or swelling is carried out under heating conditions. Further, the heating temperature is 100~130 °C.
[0035] Optionally, the heating temperature is a range of one or any two of the following: 100 ℃, 102 ℃, 104 ℃, 106 ℃, 108 ℃, 110 ℃, 112 ℃, 114 ℃, 116 ℃, 118 ℃, 120 ℃, 122 ℃, 124 ℃, 126 ℃, 128 ℃, and 130 ℃.
[0036] For example, in S2, the temperature of the oxidative chain scission reaction is any value between 130 and 180 °C, such as 130 °C, 132 °C, 134 °C, 136 °C, 138 °C, 140 °C, 142 °C, 144 °C, 146 °C, 148 °C, 150 °C, 152 °C, 154 °C, 156 °C, 158 °C, 160 °C, 162 °C, 164 °C, 166 °C, 168 °C, 170 °C, 172 °C, 174 °C, 176 °C, 178 °C, 180 °C, etc. Preferably, in S2, the temperature of the oxidative chain scission reaction is 132 °C to 175 °C. More preferably, in S2, the temperature of the oxidative chain scission reaction is 134 °C to 165 °C. More preferably, in S2, the temperature of the oxidative chain scission reaction is 135 ℃~145 ℃.
[0037] Preferably, in S2, the oxidation chain scission reaction takes 5 to 7 hours.
[0038] More preferably, in S2, the oxidation chain scission reaction takes 6 hours.
[0039] Preferably, in S2, the oxygen-containing gas is oxygen.
[0040] To facilitate a more efficient oxidative chain scission reaction, the flow rate of the oxygen-containing gas is preferably 5 mL / min or higher. Increasing the flow rate of the oxygen-containing gas does not affect the extent of the oxidative chain scission reaction, but it does result in energy waste. More preferably, the flow rate of the oxygen-containing gas is 5–50 mL / min.
[0041] After the oxidative chain scission reaction is completed, the system is cooled to room temperature, at which point a precipitated solid substance is present in the system. Subsequently, an alkaline aqueous solution is added to the system to convert the succinic acid in the system into a salt, which then enters the aqueous phase. Solid-liquid separation is then performed to obtain the filtrate and filter residue.
[0042] Preferably, the pH value of the alkaline aqueous solution is 8-10. The alkaline aqueous solution can be one or more commonly used alkaline aqueous solutions in the art, such as sodium hydroxide aqueous solution, sodium carbonate aqueous solution, or sodium bicarbonate aqueous solution. Preferably, the alkaline aqueous solution is a sodium hydroxide aqueous solution.
[0043] Preferably, the amount of the alkaline aqueous solution used is 60-100 mL / g, based on the mass of the recovered acrylonitrile-butadiene-styrene copolymer. To ensure complete conversion of succinic acid into salt, it can be added in stages, preferably more than twice.
[0044] The filtrate and filter residue were purified and extracted separately. Succinic acid was obtained from the filtrate, and carboxylated acrylonitrile-styrene copolymer was obtained from the filter residue.
[0045] Preferably, in step S3, the separation and purification includes adding an alkaline aqueous solution to the system, stirring until homogeneous, separating the solid and liquid phases to obtain a filtrate, acidifying the filtrate, crystallizing it, and filtering it to obtain succinic acid.
[0046] Preferably, the crystallization further includes a concentration step.
[0047] In this invention, the crystallization method can be one or more commonly used crystallization methods in the art, such as cooling crystallization, evaporation crystallization, dissolution crystallization, or salting-out crystallization. Preferably, the crystallization method is cooling crystallization.
[0048] As a specific example, the filtrate is acidified to pH 1-2 to ensure that the product is fully extracted, concentrated by rotation, and cooled to crystallize, thus obtaining succinic acid.
[0049] Preferably, in step S3, the separation and purification includes adding an alkaline aqueous solution to the system, stirring until homogeneous, separating the solid and liquid phases to obtain a filter residue, acidifying the filter residue, washing it until neutral, and drying it to obtain a carboxylated acrylonitrile-styrene copolymer.
[0050] The purpose of acidifying the filter residue is to convert the sodium salt of the carboxylated acrylonitrile-styrene copolymer into the carboxylated acrylonitrile-styrene copolymer. The conversion is considered complete when the pH of the filtrate no longer changes after acidification.
[0051] Compared with the prior art, the beneficial effects of the present invention include: This invention provides a method for recycling acrylonitrile-butadiene-styrene copolymer. By selecting a suitable catalyst and conditions, the polybutadiene rubber phase of the acrylonitrile-butadiene-styrene copolymer undergoes oxidative chain scission and is separated from the copolymer. After post-processing, succinic acid and / or carboxylated acrylonitrile-styrene copolymer with higher added value are obtained, realizing the effective conversion of waste plastics into other high-value-added products.
[0052] Furthermore, the method provided by this invention has the advantages of being simple to operate, environmentally friendly, and having low equipment requirements, and has good prospects for industrial application. Attached Figure Description
[0053] Figure 1The infrared spectrum of the product extracted from the filtrate of Example 1 is shown.
[0054] Figure 2 The infrared spectra of the product extracted from the filter residue of Example 1 and the recovered acrylonitrile-butadiene-styrene copolymer 1 are shown.
[0055] Figure 3 The 1H NMR spectrum is shown for the product extracted from the filter residue of Example 1 and the recovered acrylonitrile-butadiene-styrene copolymer 1.
[0056] Figure 4 The 1H NMR spectrum of the product extracted from the filter residue of Comparative Example 1 and the recovered acrylonitrile-butadiene-styrene copolymer 1 is shown. Detailed Implementation
[0057] The present invention will be further described below with reference to embodiments and comparative examples. These embodiments are merely typical descriptions of the present invention, but the present invention is not limited thereto. Unless otherwise specified, the test methods used in the following embodiments and comparative examples are conventional methods, and the raw materials and reagents used are commercially available from conventional commercial sources.
[0058] Information on the raw materials used in each embodiment and comparative example is shown in Table 1.
[0059] Table 1 Raw Material Information Table
[0060] The same reagents were used in parallel experiments of all embodiments and comparative examples of this invention.
[0061] The mass fraction of butadiene in acrylonitrile-butadiene-styrene copolymer 1 and acrylonitrile-butadiene-styrene copolymer 2 was calculated by nuclear magnetic resonance spectroscopy, and the results are shown below.
[0062] The mass fraction of butadiene in the recovered acrylonitrile-butadiene-styrene copolymer 1 was 13%. The mass fraction of butadiene in the recovered acrylonitrile-butadiene-styrene copolymer 2 was 14%.
[0063] Example 1 This embodiment provides a method for recycling and utilizing acrylonitrile-butadiene-styrene copolymer, the method comprising the following steps: S1. Add 1 g of the recycled acrylonitrile-butadiene-styrene copolymer 1 and 25 mL of N-methylpyrrolidone to a 50 mL three-necked flask, heat to 100 °C under a nitrogen atmosphere, and stir until the acrylonitrile-butadiene-styrene copolymer dissolves. After the system cools to room temperature, add 0.05 g of cobalt acetate and stir until the cobalt acetate is completely dissolved to obtain the reaction precursor. S2. Switch to an oxygen atmosphere with an oxygen flow rate of 10 mL / min, heat to 140 °C, and induce an oxidation chain scission reaction in the precursor under stirring conditions. After 6 hours of reaction, nitrogen gas is introduced again to terminate the oxidation and the mixture is cooled to room temperature. S3. Add 75 mL of sodium hydroxide aqueous solution with pH 8 to the system in two portions, stir well, and then filter to obtain filtrate and residue. S4. Add dilute hydrochloric acid to the filtrate, acidify to pH=1, concentrate by rotation, cool and crystallize to obtain succinic acid; S5. Add an appropriate amount of dilute hydrochloric acid to the filter residue for acidification until the pH value of the filtrate no longer changes after acidification. Then wash the filter residue with deionized water until neutral and dry it to obtain carboxylated acrylonitrile-styrene copolymer.
[0064] Conversion yield and product purity testing (1) Qualitative analysis of succinic acid The product extracted from the filtrate of this embodiment was characterized by infrared spectroscopy, and the results are as follows: Figure 1 As shown.
[0065] from Figure 1 It can be seen that at 1700 cm -1 A strong absorption peak appears around 2500-3300 cm⁻¹, which is attributed to the C=O stretching vibration; [the text abruptly ends here, likely due to an incomplete sentence or missing information.] -1 A broad and diffuse absorption band appears within the interval, corresponding to the stretching vibration of the OH group in carboxylic acids; at 967 cm⁻¹... -1 The absorption peaks observed around [position missing] correspond to the rocking vibration of the -CH2- group. Comprehensive analysis indicates that the product extracted from the filtrate is succinic acid.
[0066] (2) Quantitative analysis of succinic acid Based on the mass fraction of butadiene in the recovered acrylonitrile-butadiene-styrene copolymer, the succinic acid conversion yield was calculated according to the following formulas (1-1) and (1-2), and the test results are shown in Table 2.
[0067] Equation (1-1): Theoretical mass of succinic acid = (m ABS ×ω ABS中丁二烯的质量分数 (×118.09) / 54.09; Equation (1-2): Succinic acid conversion yield = actual mass of succinic acid / theoretical mass of succinic acid.
[0068] (3) Purity analysis of succinic acid The purity of succinic acid was calculated by acid-base titration using a standard alkaline solution according to the following formula (1-3), and the test results are shown in Table 2.
[0069] Equation (1-3): W = (c × V × M) / (2 × m); in: W: Purity of succinic acid (%) c: Concentration of standard NaOH solution (mol / L); V: Volume of NaOH consumed in titration (L); M: Molar mass of succinic acid (118.09 g / mol). m: Mass (g) of succinic acid sample obtained through step S4 above.
[0070] (4) Qualitative analysis of carboxylated acrylonitrile-styrene copolymer The product extracted from the filter residue in this embodiment was characterized by infrared spectroscopy and proton nuclear magnetic resonance spectroscopy. The results are as follows: Figure 2 and Figure 3 As shown.
[0071] from Figure 2 It can be seen that at 1750cm -1 A strong absorption peak appears around the [location missing], which is attributed to the C=O stretching vibration, indicating that the product extracted from the filter residue in this embodiment is a carboxylated acrylonitrile-styrene copolymer. From Figure 3 It can be seen that the peaks between 2 and 3 show the characteristic peaks of the carbon-oxygen double bond α-H in the carboxyl ester group, indicating that the product extracted from the filter residue in this embodiment is a carboxylated acrylonitrile-styrene copolymer.
[0072] (5) Quantitative analysis of carboxylated acrylonitrile-styrene copolymer When the polybutadiene rubber phase in the recovered acrylonitrile-butadiene-styrene copolymer undergoes oxidative chain scission, most of the polybutadiene structural units oxidize to form dicarboxylic acids, while the remaining small amount of butadiene structural units remain covalently bonded to the acrylonitrile-styrene segments. Simultaneously, the carbon atoms at the oxidative chain scission sites become the terminal carboxylic acid carbon groups at the ends of the acrylonitrile-styrene segments. Therefore, the actual carbon mass in the carboxylated acrylonitrile-styrene copolymer includes a small amount of carbon from the incompletely scissioned polybutadiene structural units. The fewer the number of carbon atoms in the incompletely scissioned polybutadiene structural units, the lower the actual carbon mass in the carboxylated acrylonitrile-styrene copolymer. In other words, the closer the actual carbon mass in the carboxylated acrylonitrile-styrene copolymer is to the theoretical carbon mass from the SA segment in the recovered acrylonitrile-butadiene-styrene copolymer, the higher the degree of oxidative chain scission reaction, and thus the higher the conversion yield of the carboxylated acrylonitrile-styrene copolymer. The formula for calculating the conversion yield (C) of the carboxylated acrylonitrile-styrene copolymer is shown in equation (1-4).
[0073] Equation (1-4): C = (S × Q × T) / (m × M); in: C: Conversion yield of carboxylated acrylonitrile-styrene copolymer; m: The mass percentage of carbon in the carboxylated acrylonitrile-styrene copolymer, which is calculated through elemental analysis; M: Mass of the carboxylated acrylonitrile-styrene copolymer obtained through step S5 above; S: The mass fraction of the recovered acrylonitrile-butadiene-styrene copolymer derived from the SA segment, which is calculated by nuclear magnetic resonance spectroscopy; Q: The mass percentage of carbon in the recovered acrylonitrile-butadiene-styrene copolymer, which is calculated through elemental analysis; T: The mass of the recovered acrylonitrile-butadiene-styrene copolymer.
[0074] It should be noted that calculating the conversion yield of carboxylated acrylonitrile-styrene copolymer is only meaningful when the succinic acid conversion yield is not equal to 0; conversely, when the succinic acid conversion yield is 0, it means that no carboxylated acrylonitrile-styrene copolymer is generated, and the conversion yield of carboxylated acrylonitrile-styrene copolymer is represented by " / ".
[0075] The conversion yield of the carboxylated acrylonitrile-styrene copolymer of the product extracted from the filter residue in this embodiment is shown in Table 2.
[0076] Example 2 This embodiment provides a method for recycling and utilizing acrylonitrile-butadiene-styrene copolymer, the method comprising the following steps: S1. Add 1g of the recycled acrylonitrile-butadiene-styrene copolymer 1 and 25mL of N,N-dimethylformamide to a 50mL three-necked flask. Heat to 100℃ under a nitrogen atmosphere and stir to allow the copolymer to swell until the copolymer volume no longer changes and there is no hard core or agglomeration inside. Then cool to room temperature, add 0.05g of cobalt acetate, and stir until the cobalt acetate is completely dissolved to obtain the reaction precursor. S2. Switch to an oxygen atmosphere with an oxygen flow rate of 10 mL / min, heat to 140 °C, and induce an oxidation chain scission reaction in the precursor under stirring conditions. After 6 hours of reaction, nitrogen gas is introduced again to terminate the oxidation and the mixture is cooled to room temperature. S3. Add 75 mL of sodium hydroxide aqueous solution with pH 8 to the system in two portions, stir well, and then filter to obtain filtrate and residue. S4. Add dilute hydrochloric acid to the filtrate, acidify to pH=1, concentrate by rotation, cool and crystallize to obtain succinic acid; S5. Add an appropriate amount of dilute hydrochloric acid to the filter residue for acidification until the pH value of the filtrate no longer changes after acidification. Then wash the filter residue with deionized water until neutral and dry it to obtain carboxylated acrylonitrile-styrene copolymer.
[0077] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0078] The infrared spectrum of the product extracted from the filtrate of this embodiment and the nuclear magnetic resonance hydrogen spectrum of the product extracted from the filter residue of this embodiment are basically the same as those of Example 1, indicating that the extracted products are succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively.
[0079] Example 3 This embodiment provides a method for recycling and utilizing acrylonitrile-butadiene-styrene copolymer, the method comprising the following steps: S1. Add 1g of the recycled acrylonitrile-butadiene-styrene copolymer 1 and 25mL of dimethyl sulfoxide to a 50mL three-necked flask. Heat to 100℃ under a nitrogen atmosphere and stir to allow the copolymer to swell until the copolymer volume no longer changes and there is no hard core or agglomerate inside. Then cool to room temperature, add 0.05g of cobalt acetate, and stir until the cobalt acetate is completely dissolved to obtain the reaction precursor. S2. Switch to an oxygen atmosphere with an oxygen flow rate of 10 mL / min, heat to 140 °C, and induce an oxidation chain scission reaction in the precursor under stirring conditions. After 6 hours of reaction, nitrogen gas is introduced again to terminate the oxidation and the mixture is cooled to room temperature. S3. Add 75 mL of sodium hydroxide aqueous solution with pH 8 to the system in two portions, stir well, and then filter to obtain filtrate and residue. S4. Add dilute hydrochloric acid to the filtrate, acidify to pH=1, concentrate by rotation, cool and crystallize to obtain succinic acid; S5. Add an appropriate amount of dilute hydrochloric acid to the filter residue for acidification until the pH value of the filtrate no longer changes after acidification. Then wash the filter residue with deionized water until neutral and dry it to obtain carboxylated acrylonitrile-styrene copolymer.
[0080] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0081] The infrared spectrum of the product extracted from the filtrate of this embodiment and the nuclear magnetic resonance hydrogen spectrum of the product extracted from the filter residue of this embodiment are basically the same as those of Example 1, indicating that the extracted products are succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively.
[0082] Example 4 This embodiment provides a method for utilizing the recovered acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in Example 1, except that the temperature of the oxidation chain scission reaction in S2 is different. Specifically, the temperature of the oxidation chain scission reaction is 135 °C.
[0083] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0084] The infrared spectrum of the product extracted from the filtrate of this embodiment and the nuclear magnetic resonance hydrogen spectrum of the product extracted from the filter residue of this embodiment are basically the same as those of Example 1, indicating that the extracted products are succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively.
[0085] Example 5 This embodiment provides a method for utilizing the recovered acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in Example 1, except that the temperature of the oxidation chain scission reaction in S2 is different. Specifically, the temperature of the oxidation chain scission reaction is 145 °C.
[0086] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0087] The infrared spectrum of the product extracted from the filtrate of this embodiment and the nuclear magnetic resonance hydrogen spectrum of the product extracted from the filter residue of this embodiment are basically the same as those of Example 1, indicating that the extracted products are succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively.
[0088] Example 6 This embodiment provides a method for utilizing the recovered acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in Example 1, except that the temperature of the oxidation chain scission reaction in S2 is different. Specifically, the temperature of the oxidation chain scission reaction is 175 °C.
[0089] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0090] The infrared spectrum of the product extracted from the filtrate of this embodiment and the nuclear magnetic resonance hydrogen spectrum of the product extracted from the filter residue of this embodiment are basically the same as those of Example 1, indicating that the extracted products are succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively.
[0091] Example 7 This embodiment provides a method for recovering and utilizing acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in Example 1, except that the amount of cobalt catalyst that can be dissolved in polar aprotic solvent in S1 is different. Specifically, the amount of cobalt acetate is 0.03g.
[0092] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0093] The infrared spectrum of the product extracted from the filtrate of this embodiment and the nuclear magnetic resonance hydrogen spectrum of the product extracted from the filter residue of this embodiment are basically the same as those of Example 1, indicating that the extracted products are succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively.
[0094] Example 8 This embodiment provides a method for recovering and utilizing acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in Example 1, except that the amount of cobalt catalyst that can be dissolved in polar aprotic solvent in S1 is different. Specifically, the amount of cobalt acetate is 0.07g.
[0095] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0096] The infrared spectrum of the product extracted from the filtrate of this embodiment and the nuclear magnetic resonance hydrogen spectrum of the product extracted from the filter residue of this embodiment are basically the same as those of Example 1, indicating that the extracted products are succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively.
[0097] Example 9 This embodiment provides a method for utilizing the recovered acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in Example 1, except that the oxidation chain scission reaction time in S2 is different. Specifically, the oxidation chain scission reaction time is 5 hours.
[0098] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0099] The infrared spectrum of the product extracted from the filtrate of this embodiment and the nuclear magnetic resonance hydrogen spectrum of the product extracted from the filter residue of this embodiment are basically the same as those of Example 1, indicating that the extracted products are succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively.
[0100] Example 10 This embodiment provides a method for utilizing the recovered acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in Example 1, except that the oxidation chain scission reaction time in S2 is different. Specifically, the oxidation chain scission reaction time is 7 hours.
[0101] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0102] The infrared spectrum of the product extracted from the filtrate of this embodiment and the nuclear magnetic resonance hydrogen spectrum of the product extracted from the filter residue of this embodiment are basically the same as those of Example 1, indicating that the extracted products are succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively.
[0103] Example 11 This embodiment provides a method for utilizing the recovered acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in Example 1, except that the type of cobalt catalyst that can be dissolved in polar aprotic solvents in S1 is different. Specifically, cobalt acetate is replaced with an equal mass of cobalt chloride.
[0104] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0105] The infrared spectrum of the product extracted from the filtrate of this embodiment and the nuclear magnetic resonance hydrogen spectrum of the product extracted from the filter residue of this embodiment are basically the same as those of Example 1, indicating that the extracted products are succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively.
[0106] Example 12 This embodiment provides a method for utilizing recycled acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in embodiment 1, except that the type of recycled acrylonitrile-butadiene-styrene copolymer in S1 is different. Specifically, recycled acrylonitrile-butadiene-styrene copolymer 1 is replaced with an equal mass of recycled acrylonitrile-butadiene-styrene copolymer 2.
[0107] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0108] The infrared spectrum of the product extracted from the filtrate of this embodiment and the nuclear magnetic resonance hydrogen spectrum of the product extracted from the filter residue of this embodiment are basically the same as those of Example 1, indicating that the extracted products are succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively.
[0109] Example 13 This embodiment provides a method for recycling and utilizing acrylonitrile-butadiene-styrene copolymer, the method comprising the following steps: S1. Add 50g of recycled acrylonitrile-butadiene-styrene copolymer 1 and 1.25L of N-methylpyrrolidone to a reaction vessel. Under a nitrogen atmosphere, heat the system to 100 ℃ and stir until the acrylonitrile-butadiene-styrene copolymer dissolves. After the system cools to room temperature, add 2.5g of cobalt acetate and stir until the cobalt acetate is completely dissolved to obtain the reaction precursor. S2. Switch to an oxygen atmosphere with an oxygen flow rate of 50 mL / min, heat to 140 °C, and induce an oxidation chain scission reaction in the precursor under stirring conditions. After 6 hours of reaction, nitrogen gas is introduced again to terminate the oxidation and the mixture is cooled to room temperature. S3. Add 3.75 L of sodium hydroxide aqueous solution with pH 8 to the system in two portions, stir well and filter to obtain filtrate and filter residue; S4. Add dilute hydrochloric acid to the filtrate, acidify to pH=1, concentrate by rotation, cool and crystallize to obtain succinic acid; S5. Add an appropriate amount of dilute hydrochloric acid to the filter residue for acidification until the pH value of the filtrate no longer changes after acidification. Then wash the filter residue with deionized water until neutral and dry it to obtain carboxylated acrylonitrile-styrene copolymer.
[0110] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0111] The infrared spectrum of the product extracted from the filtrate of this embodiment and the nuclear magnetic resonance hydrogen spectrum of the product extracted from the filter residue of this embodiment are basically the same as those of Example 1, indicating that the extracted products are succinic acid and carboxylated acrylonitrile-styrene copolymer, respectively.
[0112] Comparative Example 1 This comparative example provides a method for recovering and utilizing acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in Example 1, except that the type of catalyst used in S1 is different. Specifically, cobalt acetate is replaced with an equal mass of benzoyl peroxide.
[0113] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2 and... Figure 4 As shown.
[0114] from Figure 4 It can be seen that the peaks between 2 and 3 do not show the characteristic peaks of the carbon-oxygen double bond α-H in the carboxyl ester group, indicating that the polybutadiene chain was not oxidized and broken to form a carboxyl group. Therefore, the product extracted from the filter residue of this comparative example is not a carboxylated acrylonitrile-styrene copolymer.
[0115] Comparative Example 2 This comparative example provides a method for utilizing the recovered acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in Example 1, except that the temperature of the oxidation chain scission reaction in S2 is different. Specifically, the temperature of the oxidation chain scission reaction is 125 °C.
[0116] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0117] The 1H NMR spectrum of the product extracted from the filter residue of this comparative example is basically the same as that of comparative example 1, indicating that the obtained product is not a carboxylated acrylonitrile-styrene copolymer.
[0118] Comparative Example 3 This comparative example provides a method for utilizing the recovered acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in Example 1, except that the temperature of the oxidation chain scission reaction in S2 is different. Specifically, the temperature of the oxidation chain scission reaction is 185 °C.
[0119] The resulting system was completely oxidized and turned black, making separation and extraction impossible.
[0120] Comparative Example 4 This comparative example provides a method for recovering and utilizing acrylonitrile-butadiene-styrene copolymer. The method is basically the same as that in Example 1, except that the type of catalyst used in S1 is different. Specifically, cobalt acetate is replaced with an equal mass of Co / SBA-15.
[0121] The method for testing conversion yield and product purity is the same as in Example 1, and the test results are shown in Table 2.
[0122] Table 2 Test results for each embodiment and comparative example
[0123] In Table 2, " / " indicates that no carboxylated acrylonitrile-styrene copolymer was generated.
[0124] As shown in Table 2, the method for recycling acrylonitrile-butadiene-styrene copolymer provided by this invention allows the polybutadiene rubber phase of the acrylonitrile-butadiene-styrene copolymer to undergo oxidative chain scission and be separated from the copolymer. After post-processing, succinic acid and carboxylated acrylonitrile-styrene copolymer with higher added value are obtained. The conversion yield of succinic acid reaches over 50%, and the purity reaches over 78%. Simultaneously, the carboxylated acrylonitrile-styrene copolymer also exhibits a high conversion yield, exceeding 93%.
[0125] Comparing with Comparative Example 1, it can be seen that replacing the cobalt catalyst with benzoyl peroxide does not yield succinic acid and carboxylated acrylonitrile-styrene copolymer.
[0126] Comparing with Comparative Example 2, it can be seen that if the reaction temperature is too low and the reaction energy is insufficient, the polybutadiene rubber phase in the recovered acrylonitrile-butadiene-styrene copolymer cannot undergo oxidative chain scission, and thus succinic acid and carboxylated acrylonitrile-styrene copolymer cannot be generated.
[0127] Comparing with Comparative Example 3, it can be seen that if the reaction temperature is too high, it will lead to excessive oxidation of the recovered acrylonitrile-butadiene-styrene copolymer, making it impossible to obtain succinic acid and carboxylated acrylonitrile-styrene copolymer.
[0128] Comparing with Comparative Example 4, it can be seen that when the cobalt catalyst is replaced with a supported cobalt catalyst, the supported cobalt catalyst cannot be well dispersed in the polar aprotic solvent, resulting in incomplete oxidation and chain scission of the polybutadiene rubber phase in the recovered acrylonitrile-butadiene-styrene copolymer, with only a partial formation of succinic acid, so the conversion yield is only 10.5%.
[0129] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for utilizing recycled acrylonitrile-butadiene-styrene copolymer, characterized in that, The method includes the following steps: S1. Dissolve or swell the recovered acrylonitrile-butadiene-styrene copolymer with a polar aprotic solvent, and add a cobalt catalyst that can dissolve in a polar aprotic solvent to obtain the reaction precursor; S2. In an oxygen-containing gas atmosphere, the reaction precursor is subjected to an oxidative chain scission reaction at 130~175 °C. After the reaction is completed, it is cooled to room temperature in an inert atmosphere. S3. The system is separated and purified to obtain succinic acid and / or carboxylated acrylonitrile-styrene copolymer, respectively; The cobalt catalyst that can dissolve in polar aprotic solvents is an inorganic cobalt compound or an organic cobalt compound; The inorganic cobalt compound is one or more of cobalt chloride, cobalt bromide, or cobalt nitrate; the organic cobalt compound is one or more of cobalt carboxylates or cobalt complexes.
2. The method according to claim 1, characterized in that, The polar aprotic solvent is one of pyrrolidone solvents, amide solvents, or sulfoxide solvents.
3. The method according to claim 1, characterized in that, In S1, the dissolution or swelling is carried out under heating conditions.
4. The method according to claim 1, characterized in that, The mass-to-volume ratio of the recovered acrylonitrile-butadiene-styrene copolymer to the polar aprotic solvent is 1 g: 10~40 mL.
5. The method according to claim 1, characterized in that, The amount of the cobalt catalyst that is soluble in polar aprotic solvent is 0.5 to 10 wt% of the mass of the recovered acrylonitrile-butadiene-styrene copolymer.
6. The method according to claim 1, characterized in that, The oxidation chain scission reaction takes 5-7 hours.
7. The method according to claim 1, characterized in that, In S3, the separation and purification includes adding an alkaline aqueous solution to the system, stirring until homogeneous, separating the solid and liquid to obtain a filtrate, acidifying the filtrate, crystallizing it, and filtering it to obtain succinic acid.
8. The method according to claim 1, characterized in that, In S3, the separation and purification includes adding an alkaline aqueous solution to the system, stirring until homogeneous, separating the solid and liquid phases to obtain a filter residue, acidifying the filter residue, washing it until neutral, and drying it to obtain a carboxylated acrylonitrile-styrene copolymer.
Citation Information
Patent Citations
Regeneration and recovery method of carbon fiber composite material
CN121696202A
Conversion of plastic into oil
JP1997302358A